MODERASI EARNING PER SHARE DALAM MEMENGARUHI DEBT TO EQUITY RATIO DAN PRICE TO BOOK VALUE TERHADAP HARGA SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DI BEI TAHUN 2022 -2023 - Imania, Shofiatul; Wahyuni, Ika; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Financial management has a significant role in creating company value, especially in the property and real estate sector, which is known for its high asset value. This study aims to analyze the effect of Debt to Equity Ratio (DER) and Price to Book Value (PBV) on the stock price of property and real estate companies listed on the Indonesia Stock Exchange, and test the moderating role of Earning Per Share (EPS) in the relationship between the two financial ratios. The population in this study involved all property and real estate companies listed on the Indonesian Stock Exchange. Samples were taken using a purposive sampling based on specific criteria during the research period. Data analysis was carried out with a Structural Equation Modeling approach based on Partial Least Square (PLS-SEM) using Smart PLS 3. 0 software. The results of the hypothesis analysis show that both the debt-to-equity ratio (DER) and price-to-book value (PBV) significantly and positively affect stock prices. However, earnings per share (EPS) have not been proven to moderate the relationship between debt-to-equity ratio and stock price. On the other hand, Earnings Per Share is a significant amplifier of the positive relationship between Price to Book Value and Stock price.